Experience of point-of-care HbA1c testing in the English National Health Service Diabetes Prevention Programme: an observational study. Issue 2 (14th December 2020) - Barron, Emma; Misra, Shivani; English, Emma; John, W Garry; Sampson, Michael; Bachmann, Max O; Barth, Julian; Oliver, Nick; Alberti, K G M M; Bakhai, Chirag; O'Neill, Simon; Young, Bob; et al.
Abstract : Introduction: To report the observations of point-of-care (POC) glycated hemoglobin (HbA1c) testing in people with non-diabetic hyperglycemia (NDH; HbA1c 42–47 mmol/mol (6.0%–6.4%)), applied in community settings, within the English National Health Service Diabetes Prevention Programme (NHS DPP). Research design and methods: A service evaluation assessing prospectively collected national service-level data from the NHS DPP, using data from the first referral received in June 2016–October 2018. Individuals were referred to the NHS DPP with a laboratory-measured HbA1c in the NDH range and had a repeat HbA1c measured at first attendance of the program using one of three POC devices: DCA Vantage, Afinion or A1C Now+. Differences between the referral and POC HbA1c and the SD of the POC HbA1c were calculated. The factors associated with the difference in HbA1c and the association between POC HbA1c result and subsequent attendance of the NHS DPP were also evaluated. Results: Data from 73 703 participants demonstrated a significant mean difference between the referral and POC HbA1c of −2.48 mmol/mol (−0.23%) (t=157, p<0.001) with significant differences in the mean difference between devices (F(2, 73 700)=738, p<0.001). The SD of POC HbA1c was 4.46 mmol/mol (0.41%) with significant differences in SDs between devices (F(2, 73 700)=1542, p<0.001). Participants who were older, from more deprived areas and from Asian, black and mixed ethnic groups were associated with smaller HbA1c differences. Normoglycemic POC HbA1c versus NDH POC HbA1c values were associated with lower subsequent attendance at behavioral interventions (58% vs 67%, p<0.001). Conclusion: POC HbA1c testing in community settings was associated with significantly lower HbA1c values when compared with laboratory-measured referrals. Acknowledging effects of regression to the mean, we found that these differences were also associated with POC method, location, individual patient factors and time between measurements. Compared with POC HbA1c values in the NDH range, normoglycemic POC HbA1c values were associated with lower subsequent intervention attendance.